Reconstruction of meander‐bend migration from associated channel‐belt architecture recorded in successions of ancient meandering rivers: A case study from the Cretaceous Songliao Basin, China. (25th May 2021) - Lin, Zhipeng; Wang, Chengshan; Shan, Jingfu; Han, Zhongpeng; Chen, Le
Abstract: Identification of the diverse channel patterns of meander‐bend migration is essential when reconstructing the historical evolution of sedimentary processes in meandering rivers. However, reconstruction of the spatio‐temporal evolution of ancient meandering fluvial deposits for hydrocarbon exploration is difficult due to the limited research on the patterns and styles of meander‐bend migration. To reconstruct the geomorphologic and sedimentary evolution of subsurface meandering palaeochannels, this study proposes an approach based on combining meander‐bend planforms and cross‐sectional architectural elements of clastic sedimentary successions of ancient meandering rivers. The research was applied to meandering fluvial deposits of the lower Cretaceous Quantou Formation in the north‐eastern Songliao Basin, China. High‐resolution satellite images of modern meandering rivers were used to classify and evaluate the meander‐bend planform transformations of expansion, rotation and contraction (also known as bend tightening, i.e. narrowing of the neck of the meander‐bend showing a tendency towards neck tightening or cut‐off). Major meander‐bend transformations were related to cross‐sectional bedding architecture (i.e. bed dipping or bounding surface), which was identified through well‐log and core characteristics, to construct the migration patterns of subsurface meander‐belt deposits. Integration of well‐log and core analysis from a dense array of wells allowed the stratigraphic architecture of ancient meandering rivers and stacking patterns of fluvial sandbodies to be characterised. Furthermore, major reservoir architectural elements and bounding surfaces of meandering channels were identified. Ultimately, the 3D meandering fluvial architecture was represented on 2D vertical sections so that, planform transformations and the evolutionary processes of point bars and meander bends could be elucidated. Reconstruction of meander‐bend migration is of practical value for deciphering ancient fluvial systems and the development of subsurface fluvial reservoir models. Abstract : Identification and reconstruction of the diverse channel patterns are important for deciphering ancient fluvial systems and the development of subsurface fluvial reservoir models. The research reports on a novel approach used to reconstruct the geomorphologic and sedimentary evolution of the subsurface stratigraphic architecture of meandering fluvial successions. This analysis of meander‐bend migration patterns contributes to an understanding of the dynamic evolution and morphodynamic diversity of rivers that can aid evaluation and prediction of ancient and future river activity.